Oil Prices, Exchange Rates and Sectoral Stock Returns in the BRICS-T Countries: A Time-Varying Approach - Guglielmo Maria Caporale; Abdurrahman Nazif Catik; Gül Serife Huyugüzel Kisla; Mohamad Husam Helmi; Coskun Akdeniz (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses the effects of oil prices and exchange rates on sectoral stock returns in the BRICS-T countries over the period from 2 January 2001 to 22 March 2021. After estimating a benchmark linear model, the possible presence of structural breaks is investigated using the Bai and Perron (2003) tests, and a state-space model with time-varying parameters is then estimated. The main findings can be summarised as follows. Both the sub-samples and the time-varying estimates indicate a greater role for exchange rate returns. Oil prices have a positive and significant impact on the energy sector in all countries except India; a negative and significant one on the financial sector of Brazil, Russia, India, and South Africa; no effect on the transportation sector of Brazil, China, and South Africa, a negative one on those of India and Turkey, and a positive one in the case of Russia. The vulnerability of energy-dependent sectors to global fluctuations implies that appropriate energy policies should be adopted to reduce risk.
Keywords: G12; C50; C58; 330; oil prices; exchange rates; sectoral stock returns; structural breaks; time-varying parameters